Peran Dosen Dalam Mengembangkan Profil Pelajar Pancasila Melalui Perspektif Filsafat Pendidikan - Zainal Arifin; Siti Masitoh; Mochammad Nursalim (Lembaga Penelitian dan Pendidikan Mandala, 2022)
Character education in the application of the pancasila student profile in the curriculum which is a plan and arrangement that contains objectives, content, materials and teaching methods must be raised so that it has a good impact on the implementation of pancasila values focused on the role of the lecturer in shaping student attitudes and personality. The application of the pancasila student profile is expected to be able to foster motivation and character education in a student who is the responsibility of all elements. Symbolically, this sentence illustrates that the task of developing independent character for students is not an easy job, but guidance and direction is needed so that students have character. Learning on an independent campus provides challenges and opportunities for the development of innovation, creativity, capacity, personality and student needs, as well as developing independence in seeking and finding knowledge that can foster student character.